A Theory and Typology of Possession in Ob-Yenissei Languages. (17th October 2015) - Potanina, Olga; Filchenko, Andrey
Abstract: The paper outlines the on-going study of possession in Ob-Yenissei languages. The languages of the project represent the endangered indigenous idioms belonging to diverse language families and united in the study by their areal affiliation with the posited linguistic area delimited by Ob and Yenissei river basins in Western Siberia. The analysis stems from extended original and legacy fieldwork data, and addresses the key morphosyntactic and semantic features of possession within a contemporary theoretical and methodological framework, functional-cognitive grammar. The study pursues to integrate data and analysis into modern debates regarding possession from areal Siberian, genetic Uralic and wider typological perspective.